Analyzing the Financial Soundness of Kuwaiti Banks Using CAMELS Framework - AlAli, Musaed S; Al-Yatama, Sundus (Financial Risk and Management Reviews, 2019)
Evaluating the financial performance of banks has always been in the center of attention among both academics and practitioners. In that matter, CAMELS framework has always been one of the most widely used model in evaluating the financial soundness of banks and exploring the weakness areas a bank has. The model is used to distinguish good banks from bad ones. This study aims to evaluate the financial soundness of Kuwaiti banks that are listed at Kuwait stock exchange over the period 2011-2016 using CAMELS framework. Results obtained from this study showed that Ahli united bank was the top performing bank in Kuwait during the study period despite showing weakness in terms of capital adequacy and liquidity while the worst performing bank was Kuwait finance house. Kuwait finance house showed very poor performance in capital adequacy and management efficiency. The results from this research would be useful for the Kuwaiti banks to address their weak areas and try to improve on them.